Strategic CSR Responses To Subsidiary And Supplier Misconduct: A Network Perspective Of Multinationals - Grace Yulianti; Seger Santoso; Farah Qalbia (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores strategic corporate social responsibility (CSR) responses to subsidiary and supplier misconduct from a network perspective within multinational corporations (MNCs). The study synthesizes findings from scholarly articles to examine how MNCs manage ethical challenges across global supply chains. Key themes include proactive CSR strategies, stakeholder engagement, governance mechanisms, and the integration of digital technologies. The review underscores the importance of ethical sourcing decisions and firm-centric CSR practices in mitigating reputational risks and fostering sustainable business practices. While acknowledging regional variations and data limitations, the review identifies opportunities for future research, including longitudinal studies and the role of emerging technologies in enhancing supply chain transparency.